PERENCANAAN MEDIA PEMBELAJARAN DI SMK SANDIKTA BEKASI - Kahfi, Muhammad; Ulfah, Maria (Journal Education and Government Wiyata, 2024)
This research aims to gain an in-depth understanding of the integration of technology in planning learning media at SMK Sandikta Bekasi. Qualitative research methods were used, with in-depth interviews as the main data collection tool. Structured questions are designed to cover key aspects such as views on technology, the role of instructional design, evaluation of effectiveness, responsiveness to change, focus on interactivity, objectives of planning learning media, inclusivity, and steps in planning learning media. The research results show that Sandikta Bekasi Vocational School considers technology as the key to improving the quality of learning. Instructional design becomes the main foundation, while evaluating effectiveness and responsiveness to change becomes an integral part of planning. Focusing on interactivity to increase student interest and inclusivity in the accessibility of learning media are also important points. The steps in planning instructional media involve identifying needs, developing instructional objectives, selecting appropriate media, developing content, testing prototypes, and periodic evaluation.